2015
DOI: 10.1016/j.disc.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Some bounds on the neighbor-distinguishing index of graphs

Abstract: a b s t r a c tA proper edge coloring of a graph G is neighbor-distinguishing if any two adjacent vertices have distinct sets consisting of colors of their incident edges. The neighbor-distinguishing index of G is the minimum number χ ′ a (G) of colors in a neighbor-distinguishing edge coloring of G.Let G be a graph with maximum degree ∆ and without isolated edges. In this paper, we prove that χ ′ a (G) ≤ 2∆ if 4 ≤ ∆ ≤ 5, and χ ′ a (G) ≤ 2.5∆ if ∆ ≥ 6. This improves a result in Zhang et al. (2014), which state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…(1) − (3) has been proved in [13], and we only need to prove (4) and (5). If there are three consecutive vertices v i+1 , v i+2 , v i+3 ∈ N H 4,5 (v), then one of the faces incident with vv i+2 is at least a 4-face without 2-vertex or 5 + -face by Claim 10(3).…”
Section: (R3)mentioning
confidence: 88%
See 1 more Smart Citation
“…(1) − (3) has been proved in [13], and we only need to prove (4) and (5). If there are three consecutive vertices v i+1 , v i+2 , v i+3 ∈ N H 4,5 (v), then one of the faces incident with vv i+2 is at least a 4-face without 2-vertex or 5 + -face by Claim 10(3).…”
Section: (R3)mentioning
confidence: 88%
“…Conjecture 1 was confirmed by Balister et al [2] for bipartite graphs and graphs with ∆ = 3. Akbari et al [3] established that χ a (G) ≤ 3∆ for any normal graph G. This result is refined gradually to that of χ a (G) ≤ 2.5∆ + 5 in [4], to that of χ a (G) ≤ 2.5∆ in [5] and to that of χ a (G) ≤ 2∆ + 2 in [6]. By means of the probabilistic method, Hatami [7] confirmed that every normal graph G for a large enough ∆ has χ a (G) ≤ ∆ + 300.…”
Section: Introductionmentioning
confidence: 94%
“…With the aid of the minimality of G, an NDEk-coloring ϕ of H exists through the use of the color set C in which case ϕ(vv p ) = p − 1 for p ∈ [2,5]. On the basis of Claim 1, we have s ≥ 2.…”
Section: Proofmentioning
confidence: 99%
“…With the aid of the minimality of G, an NDT-k-coloring φ of H exists through the use of the color set C. In this case, φ(v) = 1 and φ(vv p ) = p for p ∈ [2,5]. The colors of the vertices v 1 , v 2 are removed.…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation